Isolation of actinomycetes from peatland to suppress the growth of Ganoderma boninense the causal agent of basal stem rot disease in oil palm - MUCHAMAD BAYU SETIYO BUDI; GIYANTO GIYANTO; EFI TODING TONDOK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Budi MBS, Giyanto, Tondok ET. 2022. Isolation of actinomycetes from peatland to suppress the growth of Ganoderma boninense the causal agent of basal stem rot disease in oil palm. Biodiversitas 23: 5914-5922. Basal stem rot is a major constrain in oil palm cultivation. The aim of this study was to obtain actinomycetes isolates that can suppress the growth of Ganoderma boninense. The research stages included rejuvenation of actinomycetes isolate stock cultures, observation of morphological characters, analysis of the potency of actinomycetes as biological control agents against G. boninense (antibiosis, volatile organic compound, effect of bioactive compounds in actinomycete culture supernatants and their concentration levels in suppressing G. boninense), physiological characterization and molecular identification was also done of selected actinomycetes. All actinomycetes colonies were grey and brown in color with rectiflexible and vertilicillate spore chain types. Three of the seven isolates tested, namely AKT19, AKT28, and AKT52, were able to suppress the growth of G. boninense up to 100% based on the dual culture test and the percent inhibition of G. boninense growth was 12.27; 17.50; and 23.23% by volatile organic compounds. At 10% concentration, the bioactive compounds of three actinomycetes isolates inhibited the growth of G. boninense, i.e., 89.17, 88.30 and 86.50%, respectively. Further results revealed that isolate AKT19 was the strongest suppressor (70.93) of G. boninense at a concentration of 0.5%, while isolates AKT 28 and 52 inhibited only 15.30 and 4.80%, respectively. All potential actinomycetes isolates produce chitinase, glucanase, cellulase, phosphatase enzymes, fixes nitrogen and secreted indole acetic acid growth hormone. Based on the analysis of 16S rRNA gene, it was noted that all potential isolates were identified as Streptomyces gelaticus.